FOLK DOLL OF LATGALE AND PRIDVINYE: THE ORIGINS OF JOINT TRADITIONS - Ostrogolovaja, Darja (Via Latgalica, 2014)
One of the most interesting and at the same time difficult questions for the researcher is to study the culture of the borderland. This is especially true for studying the areas currently disconnected, but which formed a part of a single state and have a long-term history of co-existence within it. This statement is true for the territory of Belarusian Pridvinye and Latgale, which were part of a single state for more than three hundred years. The proximity of these regions, close economic and cultural relations have caused the similarity of the material and spiritual culture of both peoples, which was reflected in traditional doll of this region.Doll, being both a child’s toy and an object having a certain ritual purpose, is an important element of the culture of the ethnos.The purpose of this research is to identify common and different features in the spiritual culture of Belarusians and Latgalians, based on such an important object of the culture of ethnos as the doll, and reveal some information about its existence, appearance, functions on the basis of ethnographic materials of the late 19th – early 20th century.The relevance of this work is due to lack of proper researches on the topic outlined above.The ethnographic data collected on the territory of the Vitebsk province and concerned to the people, who inhabited it, were used as the objects for this study. The information about the material and spiritual culture of Latgalians and Belarusians and directly about dolls of this region can be found in the works of M. Sementovskii, E. Romanov and N. Nikiforovskii, E. Voltaire. However, unfortunately, in these studies very little attention was paid to the traditional doll. Most often, this cultural object has stayed out of the range of interests of researchers in the late 19th – early 20th century. However, for example, in N. Nikiforovskii’s work there is described in details people’s attitude to the children’s games with dolls and beliefs associated with these games.The existence of several dolls both game and ritual on the territory of Belarus Pridvinye and Latgale was revealed as a result of the study. The traditional set of Belarus and Latgale toys had been formed by the end of the 19th – early 20th century. Demarcation of sacred and utilitarian areas had led to the isolation of functions of game dolls and ritual dolls. Game dolls on these territories were simple and generalized in character. Most of these dolls were made by children themselves from rags, pieces of wool, thread, ash and so on. Their main function was to entertain the child, while adults were busy. The oldest form of such type of the doll, occurring on the territory of Vitebsk province, was a doll “holova”. More sophisticated dolls, such as the “prince”, “princess”,“soldier” and others, have been also found in this area, but the data about the person, it was made by, and what games were associated with them, is practically absent. Only once they are mentioned in Nikiforovskii’s work in connection with the description of beliefs, which were widely accepted among the peasantry, that lengthy children’s games with dolls-princeses could lead to the forthcoming marriage of a family member.Ceremonial or ritual dolls have accompanied a man during the whole calendar year. Probably, Belarusians and Latvians, as well as Russians, have used dolls in all transitional type ceremonies: Christmas and Yuletide, on Shrove Tuesday, Easter, Midsummer, for the holidays associated with the beginning and the end of grazing, planting or harvest, for christenings, weddings and funerals. The study of ethnographic materials allowed accurately to detect the presence of only one doll-scarecrow of calendar type – scarecrow Mara, which was burnt during the Midsummer holiday. On the territory of the Russian empire and directly in Belarus this doll is no longer found in any of the regions. It is difficult to say, whether the person was accompanied with the doll during such holidays as Zazhinki and Dozhinki in Vitebsk province, or they were characteristic only of the Russian territories. Also, there is no definite information about the participation of dolls in rituals associated with the birth of a child. In the works of ethnographers there is mentioned the fact, that the doll was placed in the cradle, before the child was put there in order to “warm” the cradle. However, there is no information about what was this doll like, its appearance and function.To summarize, we can conclude, that there was an original doll in Latgale and Belarus. Unfortunately, because of the paucity of data on this issue in the ethnographic researches of the late 19th – early 20th century, it is hard to imagine the whole system of ritual and game dolls, that existed in this region. However, there can be no doubt about the fact, that the doll was not only the subject, that had accompanied a person at his birth and during childhood, but was an essential attribute of festive culture of Latgalians and Belarusians. The common features of Belarusian and Latgalian dolls were caused by several reasons. There were the long-term staying in a single state, the area of residence of two nations, that had been closely related with Western Dvina River as one of the main trade route, the similarity of the calendar and festive culture and, of course, peaceful, friendly attitude of the two ethnic groups to each other.All these factors had led to the formation of common cultural traditions, which were reflected in the doll of this region. The attempt to study in this paper such a phenomenon as a doll of Latgale and Belarus Pridvinye has showed the necessity for further research studies of this question in its indissoluble connection with the studying of material and spiritual culture of two nations.